Epistemologi Tauhid dalam Pendidikan Islam Implementasi Teori Islamisasi Ilmu Ismail Raji Al-Faruqi - Nadilla Aleyda Maqhfira Agustin; Usman; Ahmad Syawal (CV. ITTC INDONESIA, 2025)
This study examines the epistemology of Tawhid in Islamic education through the implementation of Ismail Raji al-Faruqi's Islamization of Knowledge theory. The research employs a qualitative approach with library research methodology, analyzing primary and secondary sources related to al-Faruqi's intellectual contributions. The study reveals that al-Faruqi's epistemological framework is built upon three fundamental dimensions: unity of knowledge, unity of life, and unity of humanity. These dimensions form a comprehensive epistemological foundation that integrates all branches of knowledge under the paradigm of Tawhid as the ultimate source of truth. The implementation of this theory in Islamic education requires systematic transformation including philosophical restructuring, curricular integration, and methodological innovation. The research findings indicate that al-Faruqi's model offers a viable solution to the dichotomy between religious and secular sciences by establishing an integrative educational framework that develops holistic human personality. This study contributes to the discourse on Islamic educational philosophy and provides practical guidelines for implementing Tawhid-based epistemology in contemporary Islamic educational institutions.